Combat stance in judo - Laterality differences between and within competition levels - Tirp, J.; Baker, J.; Weigelt, M.; Schorer, J. (International Journal of Performance Analysis in Sport, 2014)
This study examined the impact of lateral preferences (i.e. left-dominant vs. right-dominant fighting stance) on success at different levels of judo competition (German University Championships vs. German Championships vs. Olympic Games). The lateralization of the fighting stance of 840 male judoka (Olympic Games n = 204, German Championships n = 203, & German University Championships n = 433) were compared. First, a comparison of high ranked versus a normative sample was conducted. Second, statistical analyses examined the relative impact of a left-dominant vs. right-dominant fighting stance between and within competition levels. Left dominant judoka from all tournaments ranked 1st-5th were over-represented compared to athletes who ranked 7th or worse at the German University Championship. Lateral differences in fighting stance also differentiated the tournament levels, with the highest percentage of judoka fighting with a left-dominant stance at the Olympic Games. Surprisingly, there were more left dominant judoka at the German University Championship in comparison to the more competitive German Championships. No interaction between fighting stance and rankings was revealed. Lateral differences have performance implications in competitive judo; the impact of a left-dominant fighting stance on competitive success differs within and between competition levels.